Autonomic nervous system activation mediates the increase in whole‐body glucose uptake in response to electroacupuncture. Issue 8 (19th September 2017) - Benrick, Anna; Kokosar, Milana; Hu, Min; Larsson, Martin; Maliqueo, Manuel; Marcondes, Rodrigo Rodrigues; Soligo, Marzia; Protto, Virginia; Jerlhag, Elisabet; Sazonova, Antonina; Behre, Carl Johan; Højlund, Kurt; et al.
ABSTRACT: A single bout of low‐frequency electroacupuncture (EA) causing muscle contractions increases whole‐body glucose uptake in insulin‐resistant rats. We explored the underlying mechanism of this finding and whether it can be translated into clinical settings. Changes in glucose infusion rate (GIR) were measured by euglycemic–hyperinsulinemic clamp during and after 45 min of low‐frequency EA in 21 overweight/obese women with polycystic ovary syndrome (PCOS) and 21 controls matched for age, weight, and body mass index (experiment 1) and in rats receiving autonomic receptor blockers (experiment 2). GIR was higher after EA in controls and women with PCOS. Plasma serotonin levels and homovanillic acid, markers of vagal activity, decreased in both controls and patients with PCOS. Adipose tissue expression of pro‐nerve growth factor (proNGF) decreased, and the mature NGF/proNGF ratio increased after EA in PCOS, but not in controls, suggesting increased sympathetic‐driven adipose tissue metabolism. Administration of a‐/β‐adrenergic receptor blockers in rats blocked the increase in GIR in response to EA. Muscarinic and dopamine receptor antagonist also blocked the response but with slower onset. In conclusion, a single bout of EA increases whole‐body glucose uptake by activation of the sympathetic and partly the parasympathetic nervous systems, which could have important clinical implications for the treatment of insulin resistance.—Benrick, A., Kokosar, M., Hu, M., Larsson, M., Maliqueo, M., Marcondes, R. R., Soligo, M., Protto, V., Jerlhag, E., Sazonova, A., Behre, C. J., Højlund, K., Thorén, P., Stener‐Victorin, E. Autonomic nervous system activation mediates the increase in whole‐body glucose uptake in response to electroacupuncture. FASEB J . 31, 3288–3297 (2017). www.fasebj.org